(3GdeWdH GdJGe GdShj Ydi MRH GdEeGe Gdfhhjs - (3GdHcQj, eUWai Hf ceGd GdOjf Hf Ydj, J(B1162(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg GdPj Sdc HGdhGQOjf Ydi hQO GdChQGO UQGWg GdShjhHYO ajbhd eUWai Hf ceGd GdOjf GdUOjbjbO hQO Ydj GdUOjb GdMSf GdjO MSf NWjH GdNSQhjIaLQi PcQ MRHGdfhhjaCLHJ HYOe GdGWdGYs
(3BNQgG (B:s
(3ef bQC MRH GdEeGe GdfhhjUHGMG YTQ eQGJ heSGA YTQ eQGJ cGf dg eRjO GdaJM aj GdCYeGd hGdCbhGd hGdCMhGd GdXGgQI hGdHGWfIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 239s
(3eYLe GdeDdajf(B: 3 / 876s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs